(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—Voltage stability is a critical aspect of maintaining the reliable operation of modern power systems, particularly with the increasing integration of renewable energy sources, dynamic loads, and complex grid configurations. This paper presents a comprehensive analysis of voltage stability assessment techniques aimed at enhancing the overall stability and resilience of power systems. Various methodologies, including continuation power flow, modal analysis, and time-domain simulation, are explored to evaluate system performance under different operating conditions. The study emphasizes the identification of weak buses, critical voltage margins, and potential collapse points to aid in preventive control strategies. Furthermore, the role of advanced computational intelligence methods such as Artificial Neural Networks (ANN), Fuzzy Logic, and Machine Learning algorithms in improving predictive accuracy and real-time monitoring is discussed. Comparative results demonstrate the efficiency of hybrid assessment models in detecting instability precursors and optimizing reactive power compensation. The findings contribute to the development of more robust voltage stability frameworks, ensuring secure and efficient power system operation in the evolving energy landscape.